RESEARCH TRENDS ON AI-SUPPORTED COLLABORATIVE LEARNING IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOMS: A BIBLIOMETRIC ANALYSIS OF SCOPUS-INDEXED ARTICLES - Salma Tupaillah, Siti; Taufik Hidayat, Muhamad; Devi Sofyawati, Eva (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines trends in research on artificial intelligence (AI)-based collaborative learning from 2015 to 2025. In the field of education, the rapid development of artificial intelligence opens up various new possibilities, such as personalized learning, automated feedback, and interactive learning environments. However, research that comprehensively reflects developments in this field remains limited. Therefore, this study aims to identify publication trends, key contributors, and dominant research topics. The method used in this study is bibliometric analysis based on data obtained from the Scopus database. The data was analyzed using VOSviewer software to examine the growth of article publications, author productivity, country contributions, citation frequency, and co-occurrence of keywords. The results show that the number of articles increased sharply, particularly during the 2022–2025 period. The United States, China, and Hong Kong are the top countries in terms of the number of publications. Keyword analysis identified key topics in education, including artificial intelligence, collaborative learning, learning analytics, and digital innovation. In conclusion, artificial intelligence-based collaborative learning is a rapidly growing field of research with great potential to support the transition toward the education of the future.